Reviving the Rhetoric of the Christian Liberal Arts - Davis, Jeffry ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1996)
Many liberal arts colleges have moved away from the central aim of liberal arts learning--person formation for a qualitatively rich life--while still maintaining the liberal arts title. Of America's 3,400 colleges and universities, there are only 212 (6%) genuine liberal arts colleges today who do not award over 60% of their total number of annual degrees in professional fields. The vast majority of these are affiliated with a Christian church denomination or adhere to a Christian creedal stance. The art of rhetoric should be considered to articulate what liberal learning is and why it is important to educators and students. What is needed is not only a bold rhetoric, but a prophetic rhetoric which links the liberal arts message with the transcendent beliefs and values of the Bible. For a teacher at a Christian liberal arts college to possess a prophetic rhetoric, that teacher must assume, to some degree, the role of a prophet. Prophetic rhetoric challenges students toward deeper and stronger convictions about what they believe, why they learn, and how they relate to others. The rhetoric of consumerism vies for control, but is exposed and opposed by the prophetic rhetoric as it relates to the aims of education. Christian rhetoric should challenge students and instructors to consider again the reasons why they study and teach at religiously affiliated liberal arts colleges. ("A Rhetoric of Christian Liberal Arts" is attached; contains 9 references.) (CR)
ERIC Note: Paper presented at the Annual Meeting of the Conference on College Composition and Communication (47th, Milwaukee, WI, March 27-30, 1996).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Education; Christianity; Church Related Colleges; Higher Education; Liberal Arts; Outcomes of Education; Religious Factors; Rhetoric; Student Attitudes; Student College Relationship; Student Development; Student Educational Objectives; Rhetorical Stance; Liberal Arts Colleges; Speeches/Meeting Papers; Opinion Papers